A new species of Tardigrada, Platicrista ramsayi sp. nov. from the páramo of Volcán Chiles, Ecuador - Marley, Nigel J. (Zootaxa, 2006)
A new species of Eutardigrada, Platicrista ramsayi sp. nov., is described from moss samples collected at high altitude on Volcán Chiles in the Ecuadorian Andes. This species differs from all others previously described in the genus by having only oblique cuticular bars on the first three pairs of legs. Platicrista affine (Mihel…i…, 1951) is formally designated as a nomen dubium. An amendment to the diagnostic characters for Platicrista itaquasconoide is proposed. A key to the species of the genus is presented.